Application Of Pedagogical Technologies In Studying The Syntactic Meaning Of Conditions In Russian Language Lessons - Cherginskaya Irina Aleksandrovna (Euro Asian Journal Publishing, 2024)
The article raises the question of creating a textbook on methods of teaching the Russian language, where materials on modern technologies for teaching school students and developing Russian language lessons should be logically correlated, where, in particular, when studying the meaning of a condition at the level of a complex sentence, elements of such technologies are used. The logic of using in the work not exercises, but specially selected constructions from fiction texts and special case assignments, research games and supports, where students can show their knowledge, solve search problems, and demonstrate abilities in teamwork, is substantiated
Keywords: pedagogical technology; conditionality; undifferentiated and differentiated conjunctions